Przedszkole - ważny etap w życiu dziecka = Pro-health attitudes in preschool children - Wrotniewska, Małgorzata (Zielona Góra: Uniwersytet Zielonogórski, Wydział Pedagogiki, Psychologii i Socjologii)
The article is consisted of two essental issues that deal with upbringing youngsters at a preschool stage. The article plays close attention to how important role is to be a preschool teacher at the beginning of educational process. It brings to minds of us a question of definition and meaning of a word: "vision" and common lave to be preechool teacher. It shows the meaning of an adaptation case of correct and normal - emotional and physical functioning the youngsters in an preschool institution an in further live.
Keywords: przedszkole; nauczyciele; kompetencje; innowacje; kindergarten; teacher; competences; innovation